Exploring the relationship between financial literacy and business resilience: A conceptual pape - Marzaidin, Nurul Izzati; Ab Rahman , Siti Maziah; Baharuddin, Hanif; Mat Rusok, Nur Hazelen (Journal of Islamic, Social, Economics and Development, 2025)
The paper creates a conceptual model that expounds financial literacy and business resilience among Malaysian micro, small, and medium-sized enterprises (MSMEs). Business resilience refers to firms' ability to forecast, withstand, and adapt to disruptions. With the current epoch of economic shocks, technology disruption, and weather challenges, business resilience is imperative. Financial literacy—behavior, knowledge, and attitudes towards managing money—is one of the most important intangible assets that enables entrepreneurs to make informed decisions, manage cash flow, and access external finance. While important, the evidence from Southeast Asia has been inconclusive as regards the direct effect of financial literacy on resilience, with some results suggesting no weak or significant relationships. However, there is contemporary evidence that shows financial literacy, institutional support, and adaptive financial behaviors are responsible for amplifying the effect of financial literacy on resilience outcomes. Grounded on the Resource-Based View (RBV), this article positions financial literacy in a strategic intangible asset that promotes business resilience through its ability to increase preparedness, adaptability, and capacity to recover. The model suggested contributes theoretically by recognizing financial literacy as a hitherto neglected but imperative aspect of building resilience, and in practice offers evidence to policymakers and teachers as to how to integrate financial education and digital finance into SME development programs.